Desempenho de frangos de corte após vacinação com uma vacina viva atuada contra coccidiose aviária - Giacomini, Letícia da Silva (2020)
The objective of this study was to evaluate the effectiveness of vaccination against avian coccidiosis (live attenuated commercial vaccine LIVACOX® T) in the face of a challenge, and its correlation with the productive, economic performance, clinical observation and oocyst excretion in broilers. For this purpose, 420 1-day-old Cobb chicks were divided into five groups of 84 birds divided into 6 cages per group: G1. Unvaccinated and unchallenged control group; G2. Control group vaccinated with 10 ul of the vaccine on the day (zero); G3. Group challenged with 200 ul of the vaccine on day 1; G4. Group vaccinated on day (zero) and challenged on day 14; G5. Non-vaccinated group, but challenged on day 14. Vaccination by mouth was performed at a dose of 300 to 500 oocysts. After vaccination, groups 3, 4 and 5 were challenged orally with 6,000 to 10,000 oocysts (equivalent to 20 times the dose of the vaccine). During the entire period of the experiment (28 days), clinical signs were evaluated, the weight and feed conversion of the birds were evaluated, and feces were collected to evaluate the excretion of oocysts. In addition, macroscopic analysis of intestinal injuries of birds was also performed. It can be observed that both after the vaccination of groups 2, 3 and 4 and after the challenge in groups 4 and 5 there was an increase in the excretion of oocysts. In relation to clinical signs, on the 14th and 21st days in group 3, they were observed in more intense clinical signs such as weakness and lack of appetite, the feces presented with a watery and fetid consistency. In macroscopic evaluations performed on the 7th and 14th day in animals in group 3, hemorrhagic villi, presence of mucus and flaking were seen. In the analysis of weight gain, if we compare our results of final weights between groups 3 and 4, we have a difference of -105.74g per bird. Therefore, if we multiply this value by the number of birds slaughtered per day in a medium / large size refrigerator (250,000), we have an amount of 26,435 kg less chicken meat per day of slaughter, representing 581,570 kg of monthly losses (22 slaughter days), or about R $ 3,489,420.00 or U $$ 872,355.00, considering the commercial value of chicken meat at R $ 6.00 / kg or U $$ 1.5 / kg. Thus, the productive and economic impact of coccidiosis on birds is evident, and the importance of vaccination to prevent the occurrence of the disease and thus reduce losses is highlighted.